Analisis Konflik Pengupahan Antara Buruh Rokok Dan PT Gentong Gotri Semarang 2015 - Bagas Shidiq Zakaria; Priyatno Harsasto (Journal of Politic and Government Studies, 2017)
Employers and labor will always be associated, both indirectly will need each other, it is not uncommon frequent conflicts between the two. The conflict between workers and employers is a reflection of the two parties have different interests. Labor Welfare can be seen from the fulfillment of rights - the rights of workers which include wages / salaries and employment protection. What is interesting is the conflict in the cigarette factory in Semarang PT Gentong Gotri which until now still occur due to the delay in payment of wages not paid nearly one year more. The purpose of this study was to determine the cause of the problem and how to wage or the problem-solving techniques.The study was qualitative descriptive approach. Methods of data collection are interviews and observation. Informants in this study consists of 3 people, 1 employees Disnakertrans, one person and one person union workers.Discussion of the results showed that the causes of the conflict remuneration at PT Gentong Gotri is a backdrop of a change of leadership, relationships poor communication between the owner of the company with its workers, the weak economy of the enterprise, lack of talks between the two sides and the parties involved are not serious in resolving the problem this remuneration and lack of cohesiveness on the workers and their unions still are not maximized as a representative of the workers. While the real problem resolution to resolve the conflict did not exist for the moment.The conclusion is the cause of conflict this problem occurs because the non-fulfillment of the rights of workers or laborers. Until now, there has been no real settling of each - each party, from the company, workers and government. The negotiations were conducted biparit that generate their cash and installment 15,000 daily wage shortage erratic. Advice writer is a good wake Komuikasi between Integration with the workers so as to achieve the settlement of this wage issues.Keywords : Labour, Conflict, Payment